Draft Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Volume II (Statistical Portion) Union Territory of Chandigarh - Planning Commission (Planning Commission, 2002)
Major/Minor Headwise proposed Outlays for 10th Plan and Annual Plan 2002-03 Major Headwise detail of Continuing and New Schemes Physical Targets and Achievements Centrally Sponsored Schemes Pradhan Mantri Gramm Udyog Yojana - Outlay and Expenditure Financial Outlay and Expenditure for Voluntary Sector Women Component (WC) in the Stale Plan Programme-I: Financial Outlay.
Finance Department, Planning Evaluation Organisation, Chandigarh Administration